Family Law and the Internalization of Multicultural Values: A Phenomenological Study of Interfaith Couples - NOR SALAM; DWI RETNANI SRINARWATI; RUDI ADI (Universitas PGRI Kanjuruhan Malang, 2026)
This study is motivated by negative views toward multiculturalism and interfaith marriage in Indonesia. In contrast, this article views interfaith marriage and the study of multiculturalism as sociological facts rooted in the concept of Bhinneka Tunggal Ika (Unity in Diversity), the national motto of Indonesia. This study takes Tosari as its research locus, while its informants consist of seven individuals involved in interfaith marriages in the area. Methodologically, this research is a qualitative study grounded in phenomenological theory; therefore, its data collection relies on in-depth interviews. Through this method, the study produces two findings. First, the practice of interfaith marriage among interfaith couples is regarded as a manifestation of well-internalised multicultural values, particularly religious diversity as one element within the study of multiculturalism. Second, the internalisation of multicultural values among interfaith couples is typologised into two levels: the additive and the transformative.